Alcohol policies in India: A scoping review. - Jaclyn Schess; Lydia Bennett-Li; Richard Velleman; Urvita Bhatia; Alexander Catalano; Abhijeet Jambhale; Abhijit Nadkarni (PLoS ONE)
Globally, alcohol consumption causes significant societal harm and is a leading risk factor for death and disability in adults. In India, 3.7% of all deaths and 3.1% disability adjusted life years (DALYs) can be attributed to alcohol. In the context of rapid economic development and emphasized by the COVID-19 pandemic, India's lack of a consolidated and comprehensive alcohol policy has posed significant challenges to addressing this harm. In this context, the aim of our review was to undertake a comprehensive mapping of the State and national policy environment surrounding alcohol and its use in India, based on an analysis of policy documents. We did this though a scoping review of academic and grey literature, which helped to iteratively identify the websites of 15 international organizations, 21 Indian non-governmental organizations, and eight Indian Federal governmental organizations as well as State/Union Territory government sites, to search for relevant policy documents. We identified 19 Federal policy documents and 36 State level policy documents within which we have identified the specific policy measures which address the 10 categories of the World Health Organization's Global Action Plan to Reduce the Harmful Use of Alcohol. We found that there are major gaps in regulation of marketing and price controls, with much of this controlled by the States. In addition, regulation of availability of alcohol varies widely throughout the country, which is also a policy area controlled locally by States. Through the clear elucidation of the current policy environment surrounding alcohol in India, policy makers, researchers and advocates can create a clearer roadmap for future reform.